A brief overview of molecularly imprinted polymers supported on titanium dioxide matrices. (March 2019) - Sajini, T.; Gigimol, M.G.; Mathew, B.
Abstract: Molecularly imprinted polymer (MIP) is a polymer competent of mimicking selective binding of target or template molecule, which is characteristic of enzyme and antibodies. MIP has a wide range of applications in various fields of science and can be used as a sensor, catalyst, drug delivery component, etc. To overcome some demerits of MIP, the process of formation of imprinting cavity was carried out by nanoimprinting materials, which enables the imprinting technique to create more effective recognition sites than those obtained by traditional approaches. Here, in this article, we described a brief account of various discoveries happened in titanium dioxide–based molecularly imprinted polymeric system that shows a wide variety of chemical applications. The intention of this article is to provide comprehensive knowledge and information to all researchers who are interested in exploiting molecular imprinting technology toward the rational design of various chemical sensors operating on different transduction principles, ranging from electrochemical to piezoelectric, being used for the detection of different template molecules as they pose considerable impact on the understanding of the origin of life and all processes that occur in living organisms. Graphical abstract: Image 1 Highlights: Described a brief account of various discoveries happened in titanium dioxide-based MIP system. Provide an insight into the role of TiO2 in molecular imprinting technology. The topic is significant to do such summary work for new readers who are interested in molecular imprinted polymer supported on TiO2 matrices.